Readout strategies for directional dark matter detection beyond the neutrino background - O'Hare, Ciaran A.J.; Green, Anne M.; Billard, Julien; Figueroa-Feliciano, Encetali; Strigari, Louis E. (American Physical Society, 2015)
The search for weakly interacting massive particles (WIMPs) by direct detection faces an en- croaching background due to coherent neutrino-nucleus scattering. As the sensitivity of these ex- periments improves, the question of how to best distinguish a dark matter signal from neutrinos will become increasingly important. A proposed method of overcoming this so-called “neutrino floor” is to utilize the directional signature that both neutrino and dark matter induced recoils possess. We show that directional experiments can indeed probe WIMP-nucleon cross-sections below the neutrino floor with little loss in sensitivity due to the neutrino background. In particular we find at low WIMP masses (around 6 GeV) the discovery limits for directional detectors penetrate be- low the non-directional limit by several orders of magnitude. For high WIMP masses (around 100 GeV), the non-directional limit is overcome by a factor of a few. Furthermore we show that even for directional detectors which can only measure 1- or 2-dimensional projections of the 3-dimensional recoil track, the discovery potential is only reduced by a factor of 3 at most. We also demonstrate that while the experimental limitations of directional detectors, such as sense recognition and finite angular resolution, have a detrimental effect on the discovery limits, it is still possible to overcome the ultimate neutrino background faced by non-directional detectors.